Formulasi dan Evaluasi Lotion Kombinasi Magnesium Oil dan Minyak Biji Kelor (Moringa Seed Oil) - Yulyuswarni Yulyuswarni (Jurnal Kesehatan, 2021)
Magnesium plays a role in nearly 600 important metabolic and enzymatic reactions in the body. In developing countries, 10-30% of people have a magnesium deficiency. Magnesium deficiency can result in migraines, insomnia, leg cramps, anxiety, arrhythmias, diabetes mellitus, hypertension, etc. Transdermal magnesium supplementation has been shown to be useful as a muscle relaxant in treating leg cramps. Moringa Oleifera Seed Oil contains antioxidants, anti-aging, amino acids, collagen, omega 3,6 and 9, complete vitamins and minerals that are widely used in cosmetics. This experimental study aims to obtain a combination lotion formula of magnesium oil and moringa seed oil that meets the requirements and functions as an intake of magnesium and antioxidants. The data obtained were compared with the standard requirements for topical lotion preparations. The formula is designed with a magnesium chloride concentration of 250 mg / 5 ml, with four concentrations of moringa seed oil F1 (3%), F2 (6%), F3 (9%), and F4 (12%). Based on the results of the study, it was obtained that the dosage data was white, the semi-solid texture was easy to pour with a lavender aroma. All the formulas meet the requirements of pH (5,0-5,5) and some of the formulas meet the requirements of dispersion, specific gravity, viscosity. The Antioxidant activity of all formulas is very weak. Only one formula (F4) meets all the requirements for the lotion preparation.